Prospective Analyses of Circulating B Cell Subsets in ABO‐Compatible and ABO‐Incompatible Kidney Transplant Recipients. Issue 2 (23rd September 2016) - Schlößer, H. A.; Thelen, M.; Dieplinger, G.; von Bergwelt‐Baildon, A.; Garcia‐Marquez, M.; Reuter, S.; Shimabukuro‐Vornhagen, A.; Wennhold, K.; Haustein, N.; Buchner, D.; Heiermann, N.; Kleinert, R.; et al.
Abstract : Immunosuppressive strategies applied in renal transplantation traditionally focus on T cell inhibition. B cells were mainly examined in the context of antibody‐mediated rejection, whereas the impact of antibody‐independent B cell functions has only recently entered the field of transplantation. Similar to T cells, distinct B cell subsets can enhance or inhibit immune responses. In this study, we prospectively analyzed the evolution of B cell subsets in the peripheral blood of AB0‐compatible (n = 27) and AB0‐incompatible (n = 10) renal transplant recipients. Activated B cells were transiently decreased and plasmablasts were permanently decreased in patients without signs of rejection throughout the first year. In patients with histologically confirmed renal allograft rejection, activated B cells and plasmablasts were significantly elevated on day 365. Rituximab treatment in AB0‐incompatible patients resulted in long‐lasting B cell depletion and in a naïve phenotype of repopulating B cells 1 year following transplantation. Acute allograft rejection was correlated with an increase of activated B cells and plasmablasts and with a significant reduction of regulatory B cell subsets. Our study demonstrates the remarkable effects of standard immunosuppression on circulating B cell subsets. Furthermore, the B cell compartment was significantly altered in rejecting patients. A specific targeting of deleterious B cell subsets could be of clinical benefit in renal transplantation. Abstract : This prospective study describes the evolution of circulating B cell subsets following renal transplantation and a significant alteration of the B cell compartment during rejection.